Pengaruh Suhu dan Ketebalan Irisan Terhadap Kerupuk Otak-Otak Ikan Menggunakan Teknologi Vacuum Frying - Salma Hairunisa; Tamrin Tamrin; Yuni Safitri; Sandi Asmara (abe.fp.unila.ac.id, 2026)
Lampung Province is known for its enormous potential for marine and fishery resources in Indonesia. This condition will support the supply of fish for making otak-otak. Vacuum frying otak-otak can increase its shelf life, so otak-otak products have the potential for export. This study aims to analysis the effect of temperature and slice thickness in vacuum frying on the quality characteristics of fish otak-otak chips. Frying temperature and differences in slice thickness affect the quality characteristics of fish otak-otak chips, especially on the parameters of yield, colour, and crispiness, but do not significantly affect water content, taste, and aroma. Treatment with longitudinal slices divided into 3 tends to produce a crispier texture and a higher level of acceptance than whole otak-otak. The combination of 85 °C temperature with longitudinal slices resulted in the fastest frying time, namely 85 minutes, with the lowest water content of 4.0%. In contrast, the treatment of 75 °C temperature with whole slices resulted in the longest frying time, namely 139 minutes, with the highest water content of otak-otak fish at 4.7%. The best colour quality was obtained at a temperature of 75˚C with longitudinal slices with a score of 3.78, while the highest level of crispiness was obtained at a temperature of 85 °C with longitudinal slices with a score of 4.25 (crispy).